Pollinic characterization of species of the botanic family Rutaceae Juss. - Vanessa Feretti; Denise Monique Dubet da Silva Mouga (Acta Biológica Catarinense, 2016)
Species of the family Rutaceae Juss are used in the food and pharmaceutical industry, for their edible fruits and multiple medicinal properties. Aiming to complete the characterization of commercially important fruit species grown in Brazil, of melissopalynological interest, the following species were analyzed: Citrus deliciosa Ten., C. grandis (L.) Osbeck, C. limettioides Tan., C. limon (L.) Burm, C. paradisi Macfad., Citrus x sinensis var. açucar (L.) Osbeck x Citrus sinensis var. sanguinea (Engl.) Engl. and Fortunella japonica (Thunb.) Swingle. The pollen grains were prepared by acetolysis method for permanent slides. The pollen grains of all species showed up in monads, isopolars, with reticulate exine, prolate-spheroidal predominant form, mainly under circular and rectangular ambitus, radial and bilateral symmetry, average size, exine thickness from 1.68 to 3.20 µm, number of apertures between 3 to 5. Variations in relation to characterization of the group may be related to changes due to random or purposeful crosses for selection and improvement of crop plants.